Analisis Pengaruh Cash Ratio dan Claim Expense Ratio terhadap Kinerja Keuangan Perusahaan Asuransi Jiwa di BEI Tahun 2020-2023 dengan Kebijakan Dividen sebagai Mediasi - Huda, Pratiwi Nur; Albart, Nicko (Jurnal EMT KITA, 2025)
This study aims to analyze the effect of the cash ratio and claim expense ratio on the financial performance of life insurance companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023, with dividend policy as a mediating variable. This research employs a quantitative approach using path analysis techniques. The population of the study consists of life insurance companies listed on the IDX, with a sample of 18 companies selected through purposive sampling. Secondary data, including financial statements and annual reports, were obtained from the IDX website. The results indicate that: (1) the cash ratio has a significant and positive effect on the dividend payout ratio (DPR); (2) the claim expense ratio also has a significant and positive effect on DPR; (3) the cash ratio significantly and positively affects return on assets (ROA); (4) the claim expense ratio has a non-significant and negative effect on ROA; (5) DPR significantly and positively affects ROA; (6) DPR significantly mediates the effect of the cash ratio on ROA; and (7) DPR significantly mediates the effect of the claim expense ratio on ROA. This study provides theoretical implications by expanding the understanding of the interrelationship between financial variables in the life insurance sector and practical implications as a guide for financial managers in making decisions regarding the management of financial ratios and dividend policies. Future research is recommended to broaden the scope of industries studied and to consider alternative analytical methods to enrich research insights.